Effects of Some Feed Suplements Types to the Growth of Javaen Barb/Brek Fish (Puntius orphoides) Second Filial as Domestication Product - Priyo Susatyo; Sugiharto Sugiharto; Hana Hana; Titi Chasanah (Biosaintifika: Journal of Biology & Biology Education, 2016)
Aquaculture can be improved by a diversified approach in the form of domestication research  of a wild fish. The research has been done by cultivating Javaen Barb/Brek  (Puntius orphoides) from Serayu river, Banyumas at a natural pond and laboratory scale. Brek fish is relative slow in growth and development of gonad. This research is aimed to determine: (1) the rate of general growth of Brek in the provision of some kinds of additional food; (2) Relative Growth Rate (RGR); (3) Specific Growth Rate (SGR) and Feed Conversion (FC). The research used experimental methods. The method was a completely randomized design (CRD) of 4 treatments and 3 replicationsof: A = 100% pellet; B = 70% soybean sprout and 30% pellet; C = 70% Ipomoea aquatica leaf and 30% pellet; D = 35% soybean sprouts, 35% I. aquatica leaf and 30% pellet. Quantitative data were analysed by analysis of variance (ANOVA) of the fishes growth.The results show influence of feed types to the Relative Growth Rate (RGR) of Javaean Barb. The best RGR with the value of 72.40 was given by feed types in the D combination. Meanwhile, Specific Growth Rate (SGR) and Feed Conversion (FC) were not affected  by the feed types. The study were expected to provide suggestions for efficient feeding techniques in attempts at domestication of wild fish.How to CiteSusatyo, P., Sugiharto, S., Hana, H., Chasanah, T. (2016). Effects of Some Feed Suplements Types to The Growth of Javaen Barb/Brek Fish (Puntius orphoides) Second Filial As Domestication Product. Biosaintifika: Journal of Biology Biology Education, 8(3), 278-285.